Water charging in the State of São Paulo, Brazil (2007–2019): Collected and simulation of uncollected amounts - Magro, Sandro Aparecido [UNESP]; de Lima, Flaviano Agostinho [UNESP]; Biamont-Rojas, Ivan Edward [UNESP]; Almeida, Letícia Paulo; Gomes, Fabricio Cesar [UNESP]; Guandique, Manuel Enrique Gamero [UNESP] (FapUNIFESP (SciELO), 2024)
Water resource charges are fundamental for monitoring and planning effective actions to conserve, protect, and recover the Water Management Unit (UGRHI). The objective of this work was to analyze the monetary amount collected by the State of São Paulo from 2007 to 2019, considering 20 of the 22 UGRHI. It also aimed to simulate the uncollected amounts by employing three economic indices: the Fiscal Unit of the State of São Paulo (UFESP), the Broad Consumer Price Index (IPCA), and the General Price Index (IGP-M). The analysis indicates that the uncollected amount is between R$ 140 and R$ 170 million, depending on the index assessed, confirming the hypothesis that the adoption of an index would contribute significantly to water resource charges. The collected amounts are essential for investments in the Water Resource Policy of the State of São Paulo. It has not escaped the analysis that, until December 2020, there were still two UGHRI without any collection of charges.
Cobrança pelo uso da água no Estado de São Paulo, Brasil (2007-2019): Valores arrecadados e simulação de valores deixados de ser arrecadados
Keywords: collected amounts; economic index; environment; water resources charges; water resources management